IEEE 802.21 Information Services deployment for heterogeneous mobile environments - Buiati, F. (2011)
In the future mobile Internet, a key challenge is how the content is delivered to the mobile user, especially when there are multiple networks belonging to distinct operators. Knowing the network services and conditions available at each one becomes crucial. In order to store information from several networks and operators, the new IEEE 802.21 standard specifies a Media Independent Information Service (MIIS) supporting various information elements (IEs) that provide network information within a geographical area, with the aim of optimising the handover process. Since next-generation wireless devices are expected to support multiple radio access networks, users will be able to maintain connections when switching from one network to another. This article addresses a general approach towards the deployment of a Hierarchical 802.21 Information Service management infrastructure in a heterogeneous mobile environment. Through an NS-2-based simulation, it is shown that the proposed scheme improves the user experience in terms of MIIS server access time and number of optimal handovers in a random mobility scenario.